Categories of study to consider when analyzing the teaching practice of university teachers - Martínez, Milgian (Revista Innova Educación, 2022)
The improvement of teaching demands a constant analysis, reflection and criticism of the practices developed by teachers; in this sense, the objective of this article is to identify which categories should be considered when analyzing the teaching practice of university professors, as well as the aspects that are addressed from the literature when studying the processes of teaching reflection; for this, it is necessary to start from the basis of how people reach knowledge, our thinking structures, the ways in which we learn, how we reflect on our teaching practices, and the models that we create and consolidate to develop our practices. From this context, a review has been made of the approaches of different authors who, since the beginning of the 20th century, have formulated different theories regarding the beliefs, personal epistemology and didactic thinking of teachers, as well as their philosophy, approaches, didactic models and reflection processes, which influence, in one way or another, the practices they develop at the classroom level and, therefore, the way they guide their students. From our experience and based on the literature reviewed, we have identified that, when analyzing the teaching practices of university professors, some categories of thought should be considered, some intrinsic and others extrinsic, among them the beliefs about the didactic task and the context in which the professor develops, as well as his experiences, as indicated by the lifelong learning approach; likewise, the stages that professors go through to develop a reflective practice should be taken into account, starting with unconscious actions to the redefinition and reasoning of the problems